To the editorial work of Eduard Petrů - Kolářová, Jana (Bohemica Olomucensia, 2019)
The study is devoted to an overview and brief evaluation of literary historian Eduard Petrů's (1928-2006) editorial work. Petrů devoted himself to the series of literary works of older Czech literature, which he worked on throughout his professional activities. Its main goal was to make the old Czech literary texts accessible to the widest possible range of recipients, and its editions served not only to scholars, but were also a means of popularizing old Czech literature among the wider reading public.
Keywords: Eduard Petrů; editions of medieval Czech literature